A rare case of left lung agenesis in a female teenager. - Bandyopadhyay, Md Ankan; Saha, Debabrata; Saha, Kaushik; Jash, Debraj; Maji, Arnab; Banerjee, Arpita (Bangladesh Journal of Medical Science, 2012)
Pulmonary agenesis is a rare congenital anomaly. History of recurrent chest infection in first year of life is the presenting symptom although patient may be asymptomatic and detected on routine chest x-ray. Our patient presented with recurrent chest infections since childhood. CT scan thorax revealed absence of lung tissue on left side with mediastinal shifting and herniation of right lung to left side. Pulmonary angiography confirmed the diagnosis of left lung agenesis. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12610 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12